KAJIAN KARAKTERISTIK PETANI KARET DALAM MENENTUKAN PILIHAN KELEMBAGAAN TATANIAGA DI PROVINSI ACEH - Bakar, Basri A; Fauzi, Emlan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
Determining on rubber marketing institutional options is influenced by the characteristics of the institutional and socio-economic of farmers. This study aimed to examine the role of the characteristics of rubber farmers in the establishment of marketing institutional options. The research was conducted by survey method. The research has been taken in two districts of West Aceh and East Aceh. The numbers of respondents were 360 farmers. Data collection was taken by observation and structured interviews to a number of